The Analysis Biomechanics of Race Walking at the 2019 Jateng Open Championship - Hakim, Lukmanul; Rumini, Rumini; Sulaiman, Sulaiman (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2021)
Race walking is an efficient forward movement through the legs and feet supported with the hips and balanced by the arms. This race is characterized by the elements of special techniques and strictly defined by rules/conditions. The objectives of this study were: 1) Analyzing the performance of the technique of race walking through the analysis of sport biomechanics. 2) Identifying the errors of the technique of race walking. 3) Comparing the techniques of race walking from the athletes of world championship and the athletes of Jateng Open Championship in 2019. This research uses a race walking biomechanical analysis method with a mixed method of qualitative and quantitative methods with observation techniques. Check-list was used to fill the grid of the implementation of basic techniqies of race walking. Filling in the check-list carried out by expert judgment to assess the movements of the athletes. Based on the results, the male and female athletes who took part at the Central Jateng Open Championship in 2019 showed that they are in the very good category which is 8.69. The result of the technique of race walking for male with an average of 8.77 while the female was 8.61. The result of best time record for male athlete is 1 hour 49 minutes 33 seconds and the result of female athlete is 2 hours 09 minutes 52 seconds. In conclusion the technique does not always make a good timing, many factors influence the performance of the race walking such as physical, tactical, mental and external factors.